2019
DOI: 10.1002/cjoc.201900188
|View full text |Cite
|
Sign up to set email alerts
|

Study of Oxygen Vacancies on Different Facets of Anatase TiO2

Abstract: Summary of main observation and conclusion Anatase TiO2 samples with different ratios of {101} to {001} facets were prepared with hydrothermal method and further treated under three specific calcination atmospheres (air, H2, N2). The characterization results indicate that {001} facets may generate more oxygen vacancies and more Ti3+ species than {101} facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…On the optimized defect surface, the removal of O atoms from the surface of lattice strengthens the relationship between adjacent Ti atoms and other adjacent O atoms, and shortens the length of Ti-O bonds. The calculated results are consistent with the experimental ones[42].By comparing the optimized surface structures, we conducted a detailed analysis on the same position of the surface, as shown in Fig.4, and found that different concentration of oxygen vacancy causes different degree of lattice distortion of the surface structure. The O 3c on the surface of 1/8 ML oxygen vacancy relaxes upwards by 0.23 Å, and Ti v−5c and Ti v−4c relax inwardly by 0.32 and 0.28 Å, respectively, which results in the change in Ti v−5c -O-Ti v−4c on the surface structure from 94.16° to 130.21°.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…On the optimized defect surface, the removal of O atoms from the surface of lattice strengthens the relationship between adjacent Ti atoms and other adjacent O atoms, and shortens the length of Ti-O bonds. The calculated results are consistent with the experimental ones[42].By comparing the optimized surface structures, we conducted a detailed analysis on the same position of the surface, as shown in Fig.4, and found that different concentration of oxygen vacancy causes different degree of lattice distortion of the surface structure. The O 3c on the surface of 1/8 ML oxygen vacancy relaxes upwards by 0.23 Å, and Ti v−5c and Ti v−4c relax inwardly by 0.32 and 0.28 Å, respectively, which results in the change in Ti v−5c -O-Ti v−4c on the surface structure from 94.16° to 130.21°.…”
supporting
confidence: 82%
“…The g factor of the signal is equal to 1.994, which corresponds to the surface oxygen vacancies, as shown in Fig. 3b [41,42]. With the increase of aluminothermic reduction temperature, the intensity of the EPR signal becomes stronger, suggesting the increase of oxygen vacancy concentration on the surface of black TiO 2 nanotube arrays.…”
Section: Structural Characteristics Of Anatase Tio 2 Catalystsmentioning
confidence: 87%
“…On the optimized defect surface, the removal of O atoms from the surface of lattice strengthens the relationship between adjacent Ti atoms and other adjacent O atoms, and shortens the length of Ti-O bonds. The calculated results are consistent with the experimental ones[42].By comparing the optimized surface structures, we conducted a detailed analysis on the same position of the surface, as shown inFig. 4, and found that different concentration of oxygen vacancy causes different degree of lattice distortion of the surface structure.…”
supporting
confidence: 82%
“…Reduction process is usually consisting of reductive gases or reducing agents ( e.g ., H 2 , NH 3 , NaBH 4 ), which can react with oxygen atoms to produce oxygen vacancies on the surface of metal oxides. [ 12,31 ] Generally, in comparison to thermal treatment in oxygen‐deficient environment, reduction process is an easier strategy to yield oxygen vacancies in metal oxides at relatively low temperature. For example, Wang et al .…”
Section: Oxygen Defects Tailoring In Nanostructured Metal Oxidesmentioning
confidence: 99%